Linking green urbanism with walkability: the city of Alor Setar, Malaysia - Ayob, Zulkefle (2020)
The rapidity of urbanisation due to global capitalisation has caused lopsided and uneven development in many types of cities the world over. The uncontrol and unbalance development habitually initiated tribulations of environmental, social-cultural and economic problems. In Malaysia, this phenomenon has become apparent, especially in medium-sized cities. The concentration on vertical-physical development, roads and highways, and extensive business districts often disregard the human factors – the residents, workers and visitors. These cities failed to provide the quality urban environment for the urban living; poor accessibility and walkability for pedestrian mobility and lack of greeneries for a pleasant urban environment; and often disregard historical and cultural significance for monetary gains. The concept of Green Urbanism and its principals is a catalyst in solving the problems. This research focus on the overlapping of green urbanism with walkability at the Medium-sized City of Alor Setar is essential to sustain the long existence of Malaysian’s medium-sized cities.